Randomised controlled trial of non-directive counselling, cognitive-behaviour therapy, and usual general practitioner care for patients with depression. I: Clinical effectiveness. Issue 7273 (2nd December 2000) - Ward, Elaine; King, Michael; Lloyd, Margaret; Bower, Peter; Sibbald, Bonnie; Farrelly, Sharon; Gabbay, Mark; Tarrier, Nicholas; Addington-Hall, Julia
Abstract: Objective: To compare the clinical effectiveness of general practitioner care and two general practice based psychological therapies for depressed patients. Design: Prospective, controlled trial with randomised and patient preference allocation arms. Setting: General practices in London and greater Manchester. Participants: 464 of 627 patients presenting with depression or mixed anxiety and depression were suitable for inclusion. Interventions: Usual general practitioner care or up to 12 sessions of non-directive counselling or cognitive-behaviour therapy provided by therapists. Main outcome measures: Beck depression inventory scores, other psychiatric symptoms, social functioning, and satisfaction with treatment measured at baseline and at 4 and 12 months. Results: 197 patients were randomly assigned to treatment, 137 chose their treatment, and 130 were randomised only between the two psychological therapies. All groups improved significantly over time. At four months, patients randomised to non-directive counselling or cognitive-behaviour therapy improved more in terms of the Beck depression inventory (mean (SD) scores 12.9 (9.3) and 14.3 (10.8) respectively) than those randomised to usual general practitioner care (18.3 (12.4)). However, there was no significant difference between the two therapies. There were no significant differences between the three treatment groups at 12 months (Beck depression scores 11.8 (9.6), 11.4 (10.8), and 12.1 (10.3) for non-directive counselling, cognitive-behaviour therapy, and general practitioner care). Conclusions: Psychological therapy was a more effective treatment for depression than usual general practitioner care in the short term, but after one year there was no difference in outcome.